2014
DOI: 10.1051/0004-6361/201424121
|View full text |Cite
|
Sign up to set email alerts
|

TheGaia-ESO Survey: metallicity and kinematic trends in the Milky Way bulge

Abstract: Aims. Observational studies of the Milky Way bulge are providing increasing evidence of its complex chemo-dynamical patterns and morphology. Our intent is to use the iDR1 Gaia-ESO Survey (GES) data set to provide new constraints on the metallicity and kinematic trends of the Galactic bulge, exploring the viability of the currently proposed formation scenarios. Methods. We analyzed the stellar parameters and radial velocities of ∼1200 stars in five bulge fields wich are located in the region −10 • < l < 7 • and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
187
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(218 citation statements)
references
References 67 publications
30
187
1
Order By: Relevance
“…The origin of the observed metallicity gradients would then be the natural consequence of the different contribution of each of these components as a function of Galactic latitude. A similar conclusion was reached by Rojas-Arriagada et al (2014) based on the Gaia-ESO survey data.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…The origin of the observed metallicity gradients would then be the natural consequence of the different contribution of each of these components as a function of Galactic latitude. A similar conclusion was reached by Rojas-Arriagada et al (2014) based on the Gaia-ESO survey data.…”
Section: Introductionsupporting
confidence: 81%
“…The good number statistics of the total sample allows us to investigate in detail the metallicity distribution. In particular, we are interested in evaluating the decomposition of the distribution in two populations, as suggested in previous studies (Hill et al 2011;Rojas-Arriagada et al 2014). We note that Ness et al (2013a) suggested that the bulge metallicity distribution can be decomposed into five Gaussian components, each of them corresponding to different populations from the bulge and foreground disc.…”
Section: Bulge Metallicity Distributions At Constant Latitudementioning
confidence: 99%
“…There is a known metallicity gradient with latitude in the bulge, for latitudes b 5 | | > , of about −0.45 dex kpc −1 (e.g., Zoccali et al 2008;Ness et al 2013a;Rojas-Arriagada et al 2014) and a smaller gradient in longitude (e.g., Gonzalez et al 2013). The flattening of the metallicity gradient with latitude near the plane has been detected (Ramírez et al 2000;Rich et al 2007Rich et al , 2012, and the APOGEE survey now demonstrates that flattening is present not only at the minor axis but also at the entire extent of the boxy bulge (l 15°) within b | | < 2°.…”
Section: The Long Barmentioning
confidence: 99%
“…Di instead consider pure N -body simulations including a classical bulge and find that stars initially in the disc as far out as the outer Lindblad resonance of the bar contribute to the boxy bulge, comprising up to 30% of stars at high latitudes. In these scenarios, assuming that the initial disc has a declining metallicity profile, a puzzling observation is that the X-shape is weak or absent in the metal-poor stars (Ness et al 2012;Uttenthaler et al 2012;Rojas-Arriagada et al 2014). Bekki & Tsujimoto (2011) instead considered the evolution of a thin+thick disc model, where the thick disc was metal-poor and the thin disc was metal-rich.…”
Section: Introductionmentioning
confidence: 99%